Lithistid Demosponges of Deep-Water Origin in Marine Caves of the North-Eastern Mediterranean Sea - Pisera, Andrzej; Gerovasileiou, Vasilis (Frontiers in Marine Science, 2021)
Desmas-bearing demosponges known as lithistids have heavily silicified skeleton and occur typically in bathyal environments of warm and tropical areas but may be found in certain shallow marine caves. Here we report, for the first time two lithistid species, i.e., Neophrissospongia endoumensis, and N. cf. nana, that were earlier known from Western Mediterranean marine caves, from four marine caves in the north-eastern Mediterranean, and their congener Neophrissospongia nolitangere from deep waters (ca. 300 m) of the Aegean Sea. All marine caves, and sections within these caves, where lithistids occur, have freshwater springs. We interpret this surprising association between lithistids and freshwater input by elevated concentration of silica in water in cave sections where such springs occur, being 8–11 times higher in comparison with shallow water outside caves, and comparable to that of deep waters, that promoted lithistids’ development. One of the studied caves harbored an abundant population of N. endoumensis which formed large masses. The age estimation of these lithistids, based on known growth rate of related deep-water sponges, suggest that they could be approximately 769–909 years old in the case of the largest specimen observed, about 100 cm large. These sponges could have colonized the caves from adjacent deep-water areas not earlier than 7,000–3,000 years ago, after the last glaciation, because earlier they were emerged. High variability of spicules, especially microscleres, and underdevelopment of megascleres may be related to silicic acid concentration.